ZnS, CdSe and ZnSe magneto-optical and thermo-optical characteristics. (October 2022) - Mironov, Evgeniy A.; Palashov, Oleg V.; Balabanov, Stanislav S.
Abstract: In the presented work, the prospects for using pure ZnS and CdSe semiconductors for the development of Faraday isolators are investigated. Both materials have advantages over conventional magnetoactive materials. Their use can make it possible to expand the spectral range, in which isolators for high-power laser radiation can be implemented, both in the long-wavelength and short-wavelength regions. Measurements of the Verdet constant of crystals and the dependence of thermally induced depolarization caused by stress-induced birefringence on laser power were carried out. Based on the obtained experimental data, the parameters of the magneto-optical figure of merit were determined. The studied samples showed promising results, while the potential for increasing the magneto-optical figure of merit by optimizing the parameters of the production process is assessed as high. This possibility is illustrated by the example of ZnSe crystal samples obtained in various technological processes. Graphical abstract: Image, graphical abstract